Epilepsy after subarachnoid hemorrhage: the frequency of seizures after clip occlusion or coil embolization of a ruptured cerebral aneurysm: results from the International Subarachnoid Aneurysm Trial. - Hart, Y; Sneade, M; Birks, J; Rischmiller, J; Kerr, R; Molyneux, A (2011)
OBJECT: The aim of this study was to determine the probability of seizures after treatment of a ruptured cerebral aneurysm by clip occlusion and coil embolization, and to identify the risks and predictors of seizures over the short- and long-term follow-up period. METHODS: The study population included 2143 patients with ruptured intracranial aneurysms who were enrolled in 43 centers and randomly assigned to clip application or coil placement. Those patients suffering a seizure were identified prospectively at various time points after randomization, as follows: before treatment; after treatment and before discharge; after discharge to 1 year; and annually thereafter. RESULTS: Two hundred thirty-five (10.9%) of the 2143 patients suffered a seizure after randomization; 89 (8.3%) of 1073 and 146 (13.6%) of 1070 in the endovascular and neurosurgical allocations, respectively (p = 0.014). In 19 patients the seizure was associated with a rehemorrhage. Of those patients who underwent coil placement alone, without additional procedures, 52 suffered a seizure, and in the group with clip occlusion alone, 91 patients suffered a seizure. The risk of a seizure after discharge in the endovascular group was 3.3% at 1 year and 6.4% at 5 years. In the neurosurgical group it was 5.2% at 1 year and 9.6% at 5 years. The risk of seizure was significantly greater in the neurosurgical group at both 2 years and at up to 14 years (p = 0.005 and p = 0.013, respectively). The significant predictors of increased risk were as follows: neurosurgical treatment allocation, hazard ratio (HR) 1.64 (95% CI 1.19-2.26); younger age, HR 1.54 (95% CI 1.14-2.13); Fisher grade > 1 on CT scans, HR 1.34 (95% CI 0.62-2.87); delayed ischemic neurological deficit due to vasospasm, HR 2.10 (95% CI 1.49-2.94); and thromboembolic complication, HR 5.08 (95% CI 3.00-8.61). A middle cerebral artery (MCA) aneurysm location was also a significant predictor of increased risk in both groups; the HR was 2.23 (95% CI 1.57-3.17), with the probability of seizure at 6.1% and 11.5% at 1 year in the endovascular and neurosurgery groups, respectively. CONCLUSIONS: The risk of seizures after coil embolization is significantly lower than that after clip occlusion. An MCA aneurysm location increased the risk of seizures in both groups.